Effect of two different dietary protein levels on the survival rate and growth performance of Leptobarbus hosii juveniles - Ellynnawati Runge
A study was conducted at Laboratory 3, Third Floor of the Department of Animal Science and Fisheries, Universiti Putra Malaysia Bintulu Campus, to compare and observe the effects of two different dietary protein levels on the survival rate and growth performance of Leptobarbus hosii juveniles fed with two different dietary protein levels (35% and 40%) at 5% of body weight a day for 10 weeks. 60 L. hosii juveniles with initial average total length (4.08 cm) and initial average weight (0.76 g) were measured using a measuring board and a digital balance. The fish randomly distributed into 6 aquariums (30 L water volume). The fish were fed twice daily in the morning 0900 and 1700 hours in the evening. The experimental diets feeds were formulated using digestible protein and fish meal as the main source of protein. The results indicated that the effect of different dietary protein levels on survival rate and growth performance was not significantly different (p>0.05). Higher protein levels used in the experimental diets resulted in lower growth performance of L. hosii juveniles. At the end of cultured period, L. hosii juveniles showed no mortality for Treatment 1 (35% protein) and Treatment 2 (40%) protein) during 10 weeks of cultured period.